Analisis Impelementasi Kebijakan Aplikasi Qlue Di Wilayah Jakarta Utara - Rahmawati, Restu; Firman, Firman (ARISTO, 2017)
This writing going to talk about analysis the implementation of application qlue in region North Jakarta. Reason the study is done to see how the implementation of application qlue that is part of the program smart city in jakarta especially in tanjung priok. Research methodology used is the method the qualitative study descriptive to technique data collection of interview. The research results show that the implementation of the application of qlue have not been effective. It was because, the community tanjung priok many cannot discern between qlue application, is that supposed to mean lack of socialization for the public regarding the application of qlue. In addition, obliging heads of the neighborhood report three times a day also is not effective. Of the aspect of the achievement of the policy implications of the (output), application qlue policy it is implemented still not 100 percent, based on the data populi center of the community can only 35.8 % of being contented with the implementation of the application of qlue. This indicates that the target not maximum. Thus, the implementation of application qlue in North Jakarta rudimentary and consequently need to there had been improvements forward to create good governance.